Assessment in art and design education: Further reflections upon whippet-fancying and Procrustes. Issue 1 (1st March 2015) - Hickman, Richard
The reference to 'whippet-fancying' in the title refers to the notion of connoisseurship; teachers, who best know their students' abilities, play the part of the connoisseur. Procrustean references, when applied to education, refer to the tendency to trim the curriculum according to the prevailing assessment practices. There appears to have been a tendency in many developed countries to de-professionalize the profession of teaching, nowhere more so than in the area of assessment, with external examining boards making decisions about students' capabilities. Such tendencies are felt particularly harshly in the arts. This article argues for assessment practices in visual art that are student-centred and that take the form of a dialogue between teacher and student, taking into account the developing nature of a student's portfolio. I argue further that meaningful learning in art should not be pre-specified, and that the objectives model of teaching and learning is inappropriate, given our innate need to create and confer aesthetic significance.